2012
DOI: 10.1002/xrs.2395
|View full text |Cite
|
Sign up to set email alerts
|

The perspective of new multi‐layer reference materials for confocal 3D micro X‐ray fluorescence spectroscopy

Abstract: Multi‐layered components are commonly used in hi‐tech branches of modern industry. This fact generates a need for suitable reference materials for experimental examination of such specimens, and it also induces the development of mathematical procedures for quantification. To reveal experimentally the chemical composition of (multi‐)layered specimens in 3D space in a non‐destructive way, a confocal 3D micro X‐ray fluorescence spectroscopy (3D μXRF) can be employed. The scope of this paper covers preparation, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Of course, it also enables a depth elemental profiling. There are many reports of depth elemental profiling for layered materials such as paint layers [29][30][31][32][33][34][35][36][37][38][39]. The author's research group at OCU has reported a depth elemental profile for car paint chips, which have several layers depending on the type of car and manufacturing process [40].…”
Section: Confocal Micro-xrf In the Laboratorymentioning
confidence: 99%
“…Of course, it also enables a depth elemental profiling. There are many reports of depth elemental profiling for layered materials such as paint layers [29][30][31][32][33][34][35][36][37][38][39]. The author's research group at OCU has reported a depth elemental profile for car paint chips, which have several layers depending on the type of car and manufacturing process [40].…”
Section: Confocal Micro-xrf In the Laboratorymentioning
confidence: 99%
“…Beforehand, the MC algorithm requires various parameters to be specified, like chemical composition, density, and sample size as well as experimental and fundamental parameters. Czyzycki et al successfully developed a MC simulation code (monochromatic excitation) for the determination of layer thicknesses and element concentrations of various foils and multi-layer samples by deconvolution of the depth profiles [ 61 , 62 ].…”
Section: Calibration and Quantification Of Cmxrf Spectrometersmentioning
confidence: 99%
“…The thicknesses of both samples were determined under optical microscope by examination of microtome cross sections of the samples. The full description of these standards was given in ref 19. Both samples were scanned in depth with the step size of 5 μm in 36 different positions (over an area of 250 × 250 μm 2 ); the average depth profile was taken for further calculations.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%